2022
DOI: 10.1136/bmjopen-2021-058061
|View full text |Cite
|
Sign up to set email alerts
|

Work situation of patients with stroke who have returned to work: a scoping review protocol

Abstract: IntroductionThe incidence of stroke in working-age adults is increasing. Many patients face cognitive, emotional and physical impairments and their subsequent influences on returning to work. An increasing number of studies have been conducted on the transformation from unemployment to returning to work. The criteria for returning to work only used the ‘working yes/no’ as the primary outcome. Although some researchers have investigated the characteristics of patients with stroke who have returned to work, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Similarly, for adults recovering from a stroke, a common objective is the resumption of work, a goal that can substantially enhance their overall quality of life [ 33 ]. After resuming work, certain stroke patients encounter fatigue [ 34 ]. In this study, certain respondents indicated that they would give due consideration to their symptoms and make positive adjustments in their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for adults recovering from a stroke, a common objective is the resumption of work, a goal that can substantially enhance their overall quality of life [ 33 ]. After resuming work, certain stroke patients encounter fatigue [ 34 ]. In this study, certain respondents indicated that they would give due consideration to their symptoms and make positive adjustments in their jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Return to work is a common goal for adults after stroke, and can improve patient's quality of life [33]. Some stroke patients experience fatigue, etc., after returning to work [34]. Therefore, the medical staff should rst determine whether the patient can be reintegrated into society, with the help of the return-to-work selfe cacy scale [35].…”
Section: Discussionmentioning
confidence: 99%